Factors Influencing Treatment Failure Rates in Pulmonary Tuberculosis Patients - Weti; Muhammad Ihsan Hakim; Larra Fredrika; Andri Kusuma Wijaya (Institut Citra Internasional, 2026)
This study aims to determine the factors that influence the rate of treatment failure in pulmonary tuberculosis patients in the Muara Kulam Community Health Center (Puskesmas Muara Kulam). The research method used was descriptive correlative with a cross-sectional design. Data were collected using a questionnaire and analyzed using the Chi-Square test. The results showed that most patients had sufficient knowledge (69.0%), sufficient motivation (51.7%), moderate distance from their residence (50.0%), and sufficient family support (56.9%). There was a significant relationship between knowledge (p=0.001), motivation (p=0.003), distance (p=0.029), and family support (p=0.000) with treatment failure. Conclusion: Knowledge, motivation, distance from residence, and family support are factors that influence the failure of pulmonary tuberculosis treatment. Increased education and social support are needed to improve treatment success.